Integrating Local Cultural Values To Solve The Problems Of History Learning At Sma Negeri Mauta Pantar Tengah-Alor, East Nusa Tenggara - Margison A. W. B. Blegur; Leo Agung S; Cicilia Dyah (CV. Inara, 2021)
Culture is the identity of the local community that has an important role in life in the order of behavior to create harmony among people. This scientific article is written to find out how to integrate local cultural values through history learning media as the key in practicing local cultural values itself to solve the problems in the learning system. Qualitative research method was used in writing this scientific article by referring to the results of interviews from several selected informants, namely traditional leaders and history teachers, as well as several sources taken from scientific articles related to this research.